STUDYING THE MOVEMENT OF A HORIZONTAL MOVING BODY TAKING INTO ACCOUNT THE RESISTANCE OF THE ENVIRONMENT AND SOLVING RELATED PROBLEMS - M.B. Dusmuratov (Galaxy International Interdisciplinary Research Journal, 2022)
This article examines the laws of motion in the horizontal plane of a ship under the influence of the resistance force of water, as well as the impact of the resistance of air and the friction force of the surface, and issues related to them are worked out.